High speed imaging and numerical simulations of cavitation characteristic during the spreading of GaIn melt under ultrasonication. (1st May 2022) - Li, Zhengwei; Xu, Zhiwu; He, Peng; Ma, Zhongwei; Chen, Shu; Yan, Jiuchun
Highlights: Cavitation characteristics of GaIn melt during the ultrasonic-induced spreading process are studied in situ by high-speed photography. The cavitation cloud, single cavitation bubble, stable cavitation bubble, their sizes and life periods are identified. The bubble density decreases with the spreading of the droplet, which is explained by acoustic pressure. A non-cavitation region showing increasing width as the droplet spreads consistently appears at the spreading front due to the acoustic pressure loss. A cavitation threshold measuring method is proposed, and the cavitation threshold of eutectic GaIn alloy is identified to be approximately 0.65 MPa. Abstract: Cavitation is widely used in many fields, but the nature of cavitation, especially in metallic liquids, remains unclear. In this work, the cavitation bubble characteristics during the spreading of eutectic GaIn liquid droplet subjected to ultrasonication were studied in-situ by high-speed photography. The types, diameters, variations, and life cycles of cavitation bubbles were identified. Results show that the bubble density gradually decreases during the droplet spreading process because of the decreased acoustic pressure inside the thinned liquid. The cavitation presents strong/weak change characteristics with a period of dozens of acoustic periods (T, 50 µs). Cavitation clouds with large sizes and long lifetimes are observed at the early-spreading stage. Tiny cavitation bubbles emerging and collapsing within 1 T dominate the cavitation field in the late-spreading stage. Stable cavitation bubble showing continuous nucleation and collapse but minimal changes in its position is also observed. A non-cavitation region consistently appears at the spreading front because the acoustic pressure is below the cavitation threshold. The width of the non-cavitation region gradually increased as the size of the spreading area increased. A cavitation threshold measuring method is proposed based on the cavitation observation and simulation and the cavitation threshold of eutectic GaIn alloy is identified to be approximately 0.65 MPa. The cavitation bubble dynamics result shows that the cavitation bubbles with different nucleation diameters have different life periods the same growth velocity. Graphical abstract: Image, graphical abstract